2016
DOI: 10.4172/2161-1041.1000167
|View full text |Cite
|
Sign up to set email alerts
|

α-Actinin-4 Gene Mutations, Steroid Responsiveness and FSGS in Adult Onset-Nephrotic Syndrome

Abstract: Focal segmental glomerulosclerosis (FSGS) is a common pattern of injury seen in primary as well as secondary renal disorders and is a major cause of steroid-resistant nephrotic syndrome (SRNS) and end-stage kidney disease (ESKD). SRNS is defined by resistance to standard steroid therapy and it remains one of the most intractable causes of kidney failure. Mutations in α-actinin-4 gene (ACTN4) represent a frequent cause of SRNS associated with an adult onset form of FSGS. We screened a cohort of 374 subjects fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Using a greater number of samples may reveal a different possibility in the findings of this gene's connection with nephrotic syndrome in Egyptian children. A previous study evaluated 374 South Indian participants for the existence of this mutation; their classification indicated that the A763G mutation was identified only in three NS patients and not in the controls [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a greater number of samples may reveal a different possibility in the findings of this gene's connection with nephrotic syndrome in Egyptian children. A previous study evaluated 374 South Indian participants for the existence of this mutation; their classification indicated that the A763G mutation was identified only in three NS patients and not in the controls [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PCR products were electrophoresed on 2.5%, agarose gel that stained with ethidium bromide and visualized under UV light. ARMS-PCR was used for detection of NPHS2 rs3829795 according to Hashemi et al method [ 14 ] and ACTN4 rs121908415 Primers were designed based on gene sequence [ 15 ] . Briefly, two tubes were used to determine each variant for every subject.…”
Section: Methodsmentioning
confidence: 99%